Oxygen isotope composition of diatoms from Lake Emanda (northeastern Siberia, Russia) - Kostrova, Svetlana S; Biskaborn, Boris K; Pestryakova, Luidmila A; Fernandoy, Francisco; Lenz, Marlene M; Meyer, Hanno (PANGAEA, 2021)
The sedimentary sequence of core Co1412 from Lake Emanda (65°17′N; 135°45′E; 671 m a.s.l) has been retrieved in August 2017 using gravity and percussion piston corers (UWITEC Ltd., Austria) and investigated within the German-Russian 'Paleolimnological Transect' (PLOT) project. Well preserved diatoms occur only in the upper 125-cm interval of a 6.1-m sediment core covering the last 13.2 cal. ka BP. Diatoms were purified to >98% SiO₂ and <0.8% Al₂O₃ suitable for oxygen isotope analysis. The δ¹⁸O diatom values were corrected for contamination and range between +22.5‰ and +27.8‰. A new dataset on diatom oxygen isotope composition provides insights into the climate and environmental dynamics in an extreme continental setting in northeastern Siberia. The δ¹⁸O diatom record reveals an obvious shift of 2‰ in the δ¹⁸O diatom record at 11.7−11.5 cal. ka BP reflecting the onset of the Holocene. Relatively high δ¹⁸O diatom during the Early Holocene suggests relatively warm and/or dry climate with associated evaporation effects. The absolute maximum in δ¹⁸O diatom of +27.7‰ consistent with high values of diatom indices at 7.9−7.0 cal. ka BP suggests a Mid Holocene Thermal Maximum. A continuous depletion in δ¹⁸O diatom since ~5.0 cal. ka BP is interpreted as Middle to Late Holocene cooling reaching the absolute minimum at 0.4 cal. ka BP (i.e. the Little Ice Age).
Keywords: climate change; diatoms; eastern Siberia; lake sediments; stabe isotopes